1999
DOI: 10.3758/bf03201228
|View full text |Cite
|
Sign up to set email alerts
|

The role of movement in the recognition of famous faces

Abstract: The effects of movement on the recognition of famous faces shown in difficult conditions were investigated. Images were presented as negatives, upside down (inverted), and thresholded. Results indicate that, under all these conditions, moving faces were recognized significantly better than static ones. One possible explanation of this effect could be that a moving sequence contains more static information about the different views and expressions of the face than does a single static image. However, even when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
215
4
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(234 citation statements)
references
References 21 publications
13
215
4
2
Order By: Relevance
“…Indeed, a less pronounced inversion effect has been observed when faces are shown dynamically (Knappmeyer, Thornton & Bülthoff, 2003;Lander, Christie & Bruce, 1999;Hill & Johnston, 2001). More recent investigations using composite faces also support the featural influence hypothesis of facial motion perception.…”
Section: Running Head: Identity From Facial Motion 14mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a less pronounced inversion effect has been observed when faces are shown dynamically (Knappmeyer, Thornton & Bülthoff, 2003;Lander, Christie & Bruce, 1999;Hill & Johnston, 2001). More recent investigations using composite faces also support the featural influence hypothesis of facial motion perception.…”
Section: Running Head: Identity From Facial Motion 14mentioning
confidence: 99%
“…Others argue that this does not necessarily reflect a true dynamic effect though, and recognition might actually improve because the number of static frames contained within a moving sequence increases (Lander & Chuang, 2005). Lander, Christie and Bruce (1999) have however shown that when the same frames were displayed either as a static array or animated sequence, identity recognition was still significantly higher for the moving sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Christie & Bruce 56 and Bruce et al 39 report no benefits, while Pike et al 57 find advantages for study of moving items in recognition memory), but there have recently been some intriguing demonstrations that motion can aid the identification of familiar faces seen in images which are otherwise difficult to recognise. 58,59 . This suggests that as faces become familiar, their characteristic patterns of movement may become represented in memory as well as the static form.…”
Section: Current Research: Adding Dimensionsmentioning
confidence: 99%
“…For example, participants can recognize the faces of well-known politicians and celebrities more accurately from videotaped images than from static images. This finding is especially salient when the faces are presented in sub-optimal viewing formats (e.g., blurred, inverted, or pixilated displays; [60,64,66,67]). Thus it seems that motion becomes more important as a cue to identity when the viewing conditions are sub-optimal.…”
Section: Recognizing Moving Facesmentioning
confidence: 99%